Effects of acetone cyanohydrin, a derivative of cassava, on motor activity and kidney and liver function in Wistar rats - E. Rivadeneyra-Domínguez; C.J. Rosas-Jarquín; A. Vázquez-Luna; R. Díaz-Sobac; J.F. Rodríguez-Landa (Neurología (English Edition), 2019)
Introduction: Acetone cyanohydrin (ACH) is a toxic substance present in cassava roots (Manihot esculenta Crantz) which results from enzymatic hydrolysis of linamarin. Long-term consumption is associated with 2 neurological disorders: konzo and tropical ataxic neuropathy. Previous studies have evaluated behavioural alterations linked to ACH consumption, but the toxic effects of this substance on physiological processes remain unknown. Method: 32 male Wistar rats were assigned to 4 experimental groups (n = 8 per group): a vehicle group (0.3 mL saline solution, IP) and 3 ACH groups (PubChem CID: 6406) dosed at 10, 15, and 20 mM/24 hours for 28 days. We evaluated spontaneous motor activity with the open field test and motor coordination with the rotarod and forced swimming tests at 0, 7, 14, 21, and 28 days of treatment. At the end of the assessment period (day 28), blood samples were collected by transcardiac puncture to evaluate kidney and liver function. Results: ACH caused alterations in locomotor activity and promoted both lateral swimming and spinning in the forced swimming test at 21 and 28 days of treatment. Furthermore, it led to an increase in the levels of the parameters of kidney and liver function in a concentration-dependent manner, except for glucose and total bilirubin. Conclusion: Our results suggest that long-term consumption of this toxic compound present in cassava roots may be potentially dangerous for vulnerable subjects. Resumen: Introducción: La acetona cianohidrina (ACH) es una sustancia tóxica resultante de la hidrólisis enzimática de linamarina, contenido en las raíces de yuca (Manihot esculenta Crantz); su consumo a largo plazo se asocia con 2 trastornos neurológicos: konzo y la neuropatía atáxica tropical. Estudios anteriores han evaluado las alteraciones conductuales después del consumo de esta sustancia, pero los efectos tóxicos sobre los procesos fisiológicos se desconocen. Método: Se asignaron 32 ratas Wistar macho a 4 grupos experimentales (n = 8): un grupo vehículo (solución salina 0,3 ml/rata, ip) y 3 grupos con ACH (PubChem CID: 6406) a concentraciones de 10, 15 y 20 mM, durante 28 días, cada 24 h. Se evaluó la actividad motora espontánea en campo abierto y la coordinación motora en pruebas de rotarod y nado a 0, 7, 14, 21 y 28 días de tratamiento. Al final de las pruebas conductuales (día 28) se tomaron muestras de sangre por punción transcardiaca para evaluar la función renal y hepática. Resultados: La ACH promovió alteraciones en la actividad locomotora y promovió tanto el nado lateral como la conducta de giro en la prueba de nado los días 21 y 28 del tratamiento. La ACH incrementó los parámetros de la función renal y hepática de una manera dependiente de la concentración, excepto la glucosa y la bilirrubina total. Conclusión: Estos datos indican que el contenido de este compuesto tóxico contenido en las raíces de yuca podría ser potencialmente peligroso bajo el consumo a largo plazo en sujetos vulnerables. Keywords: Cassava, Acetone cyanohydrin, Motor impairment, Neurotoxic, Hepatotoxic, Nephrotoxic, Palabras clave: Yuca, Acetona cianohidrina, Alteración motora, Neurotóxico, Hepatotóxico, Nefrotóxico